One Stage Surgical Management for Third Degree Recto-vaginal Laceration in Mares: A Report of Two Cases - Pooniya, R; Jhamb, DK; Saini, R; Kumar, Satveer; Sharma, SK (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Rectovaginal lacerations in the mare occur during parturition when the foal’s limb(s) or head are forced  caudal and dorsal. The injury is seen predominantly in  primiparous mares and is usually due to violent expulsive  efforts by the mare (Colbern et al., 1985; Turner and  McIlwraith, 1989). The injury is also seen following forced  extraction of a large fetus or extraction before full dilation  of the birth canal. Third-degree perineal lacerations occur  when there is tearing through the rectovaginal septum, the  musculature of the rectum and vagina, and the perineal  body. The communication between the rectum and vagina  results in the constant presence of fecal material in the vagina.  Reconstruction of third-degree rectovaginal lacerations  is necessary to return the mare to breeding soundness.  Generally, surgery is not performed on an emergency basis.  The torn tissues are edematous and grossly contaminated;  and it is advisable to wait a minimum of 4 to 6 weeks before  attempting a repair (Turner and McIlwraith, 1989). Various  surgical techniques have been described for repairing this  condition, including repairs in one or two stages (Colbern  et al., 1985; Belknap and Nickels 1992). This paper describes  the six bite suture pattern technique (Goetz technique) for  repairing the third-degree rectovaginal laceration in mare  in one stage.